Subjetividad y acción: la filosofía de la psicología frente al psicoanálisis y el conductismo (2009)
Abstract: This research is part of the area of the philosophy of psychology that perfoms a critical review to psychological theories and approaches. The main objective is to critically evaluate two psychological approaches in particular: Freudian psychoanalysis and Skinnerian behaviorism, based on a theory of subjectivity and action. In the first part of this study, presents some key problems facing theories of subjectivity and action –such as the relationship between subjective, objective and intersubjective; the asymmetry of perspectives; the special character of self-knowledge, and the causal explanation of action– as well as some theses in response to them. The second part explains the particular theories that psychoanalysis and behaviorism develop around these issues, and develop a critical confrontation with philosophical theories defended in the first half.